Unveiling the in situ generation of a monovalent Fe(I) site in the single-Fe-atom catalyst for electrochemical CO₂ reduction - Li, Xuning (2022)
Atomically dispersed single-atom catalysts are among the most attractive electrocatalysts for the CO2 reduction reaction (CRR). To elucidate the origin of the exceptional activity of atomically dispersed Fe-N-C catalyst in CRR, we have performed operando 57Fe Mössbauer spectroscopic studies on a model single-Fe-atom catalyst with a well-defined N coordination environment. Combining with operando X-ray absorption spectroscopy, the in situ-generated four pyrrolic nitrogen atom-coordinated low-spin Fe(I) (LS FeIN4) featuring monovalent iron is identified as the reactive center for the conversion of CO2 to CO. Furthermore, density functional theory calculations reveal that the optimal binding strength of CO2 to the LS FeIN4 site, with strong orbital interactions between the singly occupied dz2 orbital of the Fe(I) site and the singly occupied π∗ orbital of [COOH] fragment, is the key factor for the excellent CRR performance.